In vitro and in vivo anti-tumor activity of Antrodia salmonea against twist-overexpressing HNSCC cells: Induction of ROS-mediated autophagic and apoptotic cell death. (February 2023) - Yang, Hsin-Ling; Lin, Yi-An; Pandey, Sudhir; Liao, Jiunn-Wang; Way, Tzong-Der; Yeh, Yu-lyu; Chen, Siang-Jyun; Hseu, You-Cheng
Abstract: Head and neck squamous cell carcinoma (HNSCC) is a relatively common malignancy, characterized by lethal morbidity. Herein, we attempted to investigate the autophagy/apoptosis activities of the submerged fermented broths of Antrodia salmonea (AS) in HNSCC Twist-overexpressing (OECM-1 and FaDu-Twist) cells. AS (0–150 μg/mL) effectively reduced cell viability, colony formation, and downregulated Twist expression in OECM-1 and FaDu-Twist cells compared to FaDu cells. AS- induced apoptosis was mainly associated with activation of caspase-3, PARP cleavage, increased expression of VDAC-1 and disproportionation of Bax/Bcl-2. Annexin V/PI staining suggested late apoptosis induction by AS treatment. AS exhibits enhanced autophagy process mediated via LC3-I/II accumulation, increased acidic vesicular organelles (AVOs) formation and p62/SQSTM1 expression feeding into the apoptotic program. However, pre-treatment with autophagy blockers 3-MA and CQ significantly diminished AS-induced cell death. Additionally, suppression of AS-induced ROS release by treatment with antioxidant N -acetylcysteine (NAC) resulted in reduction of apoptotic and autophagic cell death. In vivo studies strengthened the above observations and showed that AS effectively reduced the tumor volume and tumor weight in OECM-1-xenografted nude mice. This study discovered that Antrodia salmonea exhibits a novel anti-cancer mechanism which could be harnessed as a new potent drug for HNSCC treatment.